Respuestas

  • Usuario de Brainly
2013-03-09T20:29:27+01:00

a)1 - 2x +4=11 -5x

1 + 4 - 11 = - 5x + 2x

- 6 = - 3x

-6/-3 = x

 2 = x

 

b)5 + 3(2x -1) -3x=x  + 3

5 + 6x - 3 - 3x = x + 3

3x - x = 3 + 3 - 5

2x = 1

x = 1/2

 

c)1 - 2(x -3) +3x=3(x-1)+2

1 - 2x + 6 + 3x = 3x + 3 + 2

1+ 6 - 3 - 2 = 3x - 3x + 2x

2 = 2x

 2/2 =x

 1 =x

 

d) 7 -3 (x-1) + x =2(x +1) - 6

7 - 3x + 3 + x = 2x + 2 - 6

7 + 3 + 6 - 2 = 2x + 3x - x

14 = 4x

14/4 = x

7/2 =x

 

e) 1 -(4x - 2)+ 2x= 1 - x

1 - 4x + 2 + 2x = 1 - x

1 + 2 -1 = - x + 4x - 2x

2 = x

 

 

espero que te sirva, salu2!!!